2008
DOI: 10.1002/cjas.53
|View full text |Cite
|
Sign up to set email alerts
|

Concentration de l'actionnariat, séparation des droits de vote et des droits de propriété et gestion des bénéfices: Une étude empirique canadienne

Abstract: Drawing from models of Jones (1991) and Kothari, Leone, and Wasley (2005), this study examines the relationship between Canadian corporate ownership structure and earnings management from 1995 to1999. There is evidence of a nonmonotonic relationship. The concentration of voting and cash flow rights with the ultimate owner first increases earnings management, but as the level of ownership concentration increases, earnings management decreases. There is also a positive correlation between earnings management and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 55 publications
(75 reference statements)
3
14
0
4
Order By: Relevance
“…These authors show that earnings management incentives for French firms are specifically linked to contractual debt costs. On the other hand, supervision by the creditors may also allow for better governance and thus contribute to the reduction of managers' flexibility when it comes to managing earnings (Bozec, 2008). Therefore, in our study, we expect that the level of earnings management, after adopting IAS/IFRS, is related to the company's debt levels.…”
Section: Debtmentioning
confidence: 90%
See 2 more Smart Citations
“…These authors show that earnings management incentives for French firms are specifically linked to contractual debt costs. On the other hand, supervision by the creditors may also allow for better governance and thus contribute to the reduction of managers' flexibility when it comes to managing earnings (Bozec, 2008). Therefore, in our study, we expect that the level of earnings management, after adopting IAS/IFRS, is related to the company's debt levels.…”
Section: Debtmentioning
confidence: 90%
“…In fact, some studies have found a positive relationship between company size and financial statement reliability (Bédard et al, 2004;McMullen, 1996). In addition, large firms usually produce more information of better quality than smaller companies and their activities are monitored more closely by financial analysts, which could limit the earnings management (Bozec, 2008). Therefore, in our research, we expect that the level of earnings management, after adopting IAS/IFRS, is linked to the company's size.…”
Section: Control Variablesmentioning
confidence: 92%
See 1 more Smart Citation
“…Ding et al [19] provided evidence that the link between magnitude of earnings management of Chinese companies and ownership concentration can be described by an inverted U-shaped model. Bozec [46] provided evidence that there is a nonmonotonic relationship between ownership structures and earnings management. The ownership concentration of the supreme owner at first stage increases earnings management, but as the level of ownership concentration increases, earnings management is reduced.…”
Section: Shareholder Concentration and Earnings Managementmentioning
confidence: 99%
“…This variable was used by Bozec (2008); Ding et al (2007); et Liu et Lu (2007) who argue that the concentration of ownership decreases earnings management. Also, a study conducted by Rao et Lee-Sing (1995) showed that 55% of Canadian companies are controlled by dominating shareholders; therefore it is important to control for the concentration of ownership…”
Section: Ownership Concentrationmentioning
confidence: 99%